Nghiên cứu lý thuyết phản ứng tách hiđro giữa gốc metyl với một số anđehit - Cường, Ngô Tuấn; Thùy, Phan Thị; Nam, Trương Văn; Hoàn, Phạm Thọ; Hưng, Trần Hữu; Minh Huệ, Nguyễn Thị (Vietnam Journal of Chemistry, 2017)
Hydrogen abstraction reactions between the methyl radical and some aldehydes (CnH2n+1CHO, n = 0÷3) have been studied by the Density Functional Theory (DFT) using the B3LYP functional combined with the 6-311++G(d,p) and 6-311+G(3df,2p) basis sets. We have identified pathways of forming the methane and aldehyde’s radicals. Our results show that the energy barrier of these pathways ranges from 20.1 to 53.1 kJ/mol. Values of the barrier height and local softness also indicate that the methyl radical reacts easily with hydrogen atoms closed to the functional group position for any andehyde’s isomers. Keywords. Reaction abstraction, ankanal (RCHO), methyl radical (CH3), Density Functional Theory, B3LYP, PES